2018
DOI: 10.1002/btpr.2651
|View full text |Cite
|
Sign up to set email alerts
|

A generalized purification step for viral particles using mannitol flocculation

Abstract: Vaccine manufacturing has conventionally been performed by the developed world using traditional unit operations like filtration and chromatography. There is currently a shift in the manufacturing of vaccines to the less developed world, requiring unit operations that reduce costs, increase recovery, and are amenable to continuous manufacturing. This work demonstrates that mannitol can be used as a flocculant for an enveloped and nonenveloped virus and can purify the virus from protein contaminants after micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…Changes in electrostatic and hydrophobic interactions can result in either intraparticle or interparticle interactions. The flexible smaller proteins are known to undergo conformational changes (intraparticle interactions) in the presence of osmoprotectants (Auton et al, 2011; Street et al, 2006) and comparatively rigid viruses have been shown to flocculate (interparticle interactions) (Gencoglu & Heldt, 2015; Gencoglu et al, 2014; Heldt et al, 2018) in the presence of similar osmolytes. In this study, the osmolytes induced interfacial interactions between virus particles and the PEG‐rich phase to improve virus recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in electrostatic and hydrophobic interactions can result in either intraparticle or interparticle interactions. The flexible smaller proteins are known to undergo conformational changes (intraparticle interactions) in the presence of osmoprotectants (Auton et al, 2011; Street et al, 2006) and comparatively rigid viruses have been shown to flocculate (interparticle interactions) (Gencoglu & Heldt, 2015; Gencoglu et al, 2014; Heldt et al, 2018) in the presence of similar osmolytes. In this study, the osmolytes induced interfacial interactions between virus particles and the PEG‐rich phase to improve virus recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Osmoprotectants have been utilized to reduce intermolecular interactions, thereby inducing intramolecular interactions to stabilize protein biologics in final formulations (Lee 2000; Wlodarczyk et al, 2018). Conversely, osmolytes have been shown to induce intermolecular interactions to flocculate viruses (Gencoglu & Heldt, 2015; Gencoglu et al, 2014; Heldt et al, 2018), which aided in the development of filtration‐based methods for virus purification. The exact mechanism of osmolyte function in protein stabilization or viral flocculation, however, is not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Osmolyte mannitol has been used as a flocculant for PPV and SINV and can purify the flocculated viruses from protein contaminants after microfiltration. A 58-96% virus recovery and an 80% of contaminated protein removal could be achieved [148].…”
Section: Detection Of Specific Viruses Using Aunpsmentioning
confidence: 99%
“…Viruses tend to attract each other and form aggregations. The osmolyte effect on virus and protein stability is shown in Figure 2.14 [148]. Thus, protecting osmolytes can be used as virus flocculants [142,143].…”
Section: Detection Of Specific Viruses Using Aunpsmentioning
confidence: 99%
See 1 more Smart Citation